Lasso Peptide Benenodin‑1 Is a Thermally Actuated [1]Rotaxane Switch - Zong, Chuhan; Wu, Michelle J; Qin, Jason Z; Link, A. James (Journal of the American Chemical Society, 2017)
Mechanically interlocked molecules that change their conformation in response to stimuli have been developed by synthetic chemists as building blocks for molecular machines. Here we describe a natural product, the lasso peptide benenodin-1, which exhibits conformational switching between two distinct threaded conformers upon actuation by heat. We have determined the structures of both conformers and have characterized the kinetics and energetics of the conformational switch. Single amino acid substitutions to benenodin-1 generate peptides that are biased to a single conformer, showing that the switching behavior is potentially an evolvable trait in these peptides. Lasso peptides such as benenodin-1 can be recognized and cleaved by enzymes called lasso peptide isopeptidases. We show that only the native conformer of benenodin-1 is cleaved by its cognate isopeptidase. Thus, thermally induced conformational switching of benenodin-1 may also be relevant to the biological function of these molecules.